The comparison of the effects of hepatic regeneration after partial hepatectomy, silybum marinaum, propofol, N-acetylcysteine and vitamin E on liver - BÜLBÜLOĞLU, ERTAN; Yormaz, S.; Bulbuloglu, ERTAN; Kurutas, E. B.; Ciralik, H.; Yuzbasioglu, M. F.; Yildiz, H.; Coskuner, I; Silay, E.; Kantarceken, B.; Goksu, M.; Senoglu, N.; et al. (My University, 2012)
Aim: We investigated the comparison of the effects of N-acetylcysteine, silybum marinaum, propofol, and vitamin E on liver hepatic regeneration after partial hepatectomy.